A new approach to institutional domain analysis: multilevel research fronts structure - Miguel, Sandra (2008)
The intellectual structure and main research fronts of the Faculty of Natural Sciences and Museum of the National University of La Plata, Argentina is studied, based on the cocitation analysis of subject categories, journals and authors of their scientific publications collected in the Science Citation Index, CD-ROM version, for the period 1991?2000. The objective of this study is to test the utility of those techniques to explore and to visualize the intellectual structure and research fronts of multidisciplinary institutional domains. Special emphasis is laid on the identification of multilevel structures, by means of arrangements of subject categories cocitation analysis and journal cocitation analysis.